Morphological characterization, seed production, and oil content of several lemongrass (Cymbopogon citratus (D.C.) Stapf.) Line - Setiadi, Adi; Syukur, Cheppy; Holid, Idam; Lindiana, Lindiana (Universitas Padjadjaran, 2024)
Cymbopogon citratus, commonly known as lemongrass, is a perennial herb widely cultivated for its culinary, medicinal, and aromatic industries. This research investigates the morphological characterization and potential yield of different lemongrass lines. The study involved the collection of diverse lemongrass genotypes from various geographic regions in Indonesia. The research was conducted using a randomized block design with three replications. Morphological character observations encompass both quantitative and qualitative characters of plants. Morphological characteristics such as plant height, leaf length and width, stem diameter, and number of tillers were measured to assess the variations among the genotypes. The results revealed considerable variability in the morphological traits among the lemongrass. Plant height ranged from 102.28 to 158.96 cm, while stem length and diameter varied between 26.11 to 42.61 cm and 8.99 to 19.68 cm, respectively. The number of tillers per plant ranged from 7.59 to 49.41. Moreover, the essential oil content varied from 0.07% to 0.26% (v/w). According to correlation analysis, the stem's diameter and the leaf's width positively correlate with the essential oil content. As a result, we can continue to develop the Sukabumi local line to maximize biomass and essential oil yields.